Open BIM structural modelling and design analysis on double storey reinforced concrete terrace residential house - Goh, Yi Han (2022)
The construction industry plays a significant role in promoting economic growth and social stability in every country. The conventional construction method which adopts the manual design calculation is proven to be time consuming and inconsistent has led to the events of project delay and over budget. Meanwhile, the building information modelling (BIM) method which utilizes the software in performing modelling and design works is an alternative or replacement to the conventional method. The industry is well aware of the existence of the BIM tools in the market. However, due to factors such as high overhead cost and unexperienced BIM modeller, only a certain number of industry players have invested on the BIM concept design. This study aims to model and design a double storey reinforced concrete house using open BIM tools and compare with the actual as-built design. The open BIM method utilizes software from different vendors whereby in this study, Autodesk Revit and SCIA Engineer is utilized for modelling and structural analysis respectively. The structural frame is constructed in Autodesk Revit based on the architecture and C&S as-built drawings. The structural model which consist of structural beam, slab and columns are exported to SCIA Engineer to perform load assignation and structural analysis on the structural model. Hence, the critical structural elements which comprises of beam, slab and columns are identified. The first model is designed with the as-built reinforcement design. In the meantime, the reinforcement design in accordance to the European Code 2 are performed on the critical structural elements which results in another model with a new reinforcement design. Upon the addition of the new reinforcement designs, capacity check indicates modified reinforcement is required for the first floor beam and column. The two structural model with different reinforcement design are exported back to Autodesk Revit for quantity take off. The result of the quantity take-off present that the cost of structural material usage for the as-built model and the new model are RM 146,497.59 and RM 137,753.63 respectively whereby the percentage difference on the cost for the two design are 5.97%. In a nutshell, this study concludes that the BIM design approach has a more effective material usage which provides a more economical design compared to the conventional design.